2008
DOI: 10.1158/0008-5472.can-07-6178
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Cooperative Genetic Changes That Temporally Drive Alveolar Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma of childhood and adolescence. Despite advances in therapy, patients with a histologic variant of RMS known as alveolar (aRMS) have a 5-year survival rate of <30%. aRMS tissues exhibit a number of genetic changes, including lossof-function of the p53 and Rb tumor suppressor pathways, amplification of MYCN, stabilization of telomeres, and most characteristically, reciprocal translocation of loci involving the PAX and FKHR genes, generating the PAX7-FK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 21 publications
5
77
0
Order By: Relevance
“…Several studies have reported phosphorylation in the PAX3 domain of PAX3-FKHR in association with its transcriptional activity. 1,[54][55][56][57][58] However, none of the above studies reported phosphorylation-induced we did perceive, during the assessment of PAX3-FKHR transactivation potency in ARMS cells, that PAX3-FKHR appears as a doublet of a faster and slower migrating form. Interestingly, the data showed the shift of PAX3-FKHR to a slower migrating form in ARMS cells grown in DM.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Several studies have reported phosphorylation in the PAX3 domain of PAX3-FKHR in association with its transcriptional activity. 1,[54][55][56][57][58] However, none of the above studies reported phosphorylation-induced we did perceive, during the assessment of PAX3-FKHR transactivation potency in ARMS cells, that PAX3-FKHR appears as a doublet of a faster and slower migrating form. Interestingly, the data showed the shift of PAX3-FKHR to a slower migrating form in ARMS cells grown in DM.…”
Section: Discussionmentioning
confidence: 66%
“…Mathivanan Jothi, 1 Kochi Nishijo, 2, † Charles Keller 3 and Asoke K. Mal 1, transactivation power and relaxed target specificity, leading to deregulated expression of downstream targets that cause ARMS phenotype. A typical feature of ARMS also includes the myogenic phenotype with expression of MyoD, 14 a bona fide target of PAX3-FKHR, 13,15 which acts as a key regulator of myogenic gene expression, leading to terminal differentiation.…”
Section: Akt and Pax3-fkhr Cooperation Enforces Myogenic Differentiatmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhabdomyosarcoma is a disease that has a steady incidence throughout childhood (aRMS contrasts dramatically with eRMS, the latter of which peaks with toddler and adolescent growth spurts) (Ognjanovic et al 2009). Suggestion of Myf6 + prenatal or postnatal myogenic cells, possibly a terminally differentiating subpopulation, as an aRMS cell of origin was first reported by our group (Keller et al 2004a,b) and later complemented by in vitro studies of human postnatal myoblasts transformed by PAX3:FOXO1 and other cooperative initiating mutations (Naini et al 2008). Congenital fusion-positive aRMS is rarely reported, and congenital aRMS is generally fusion-negative (Godambe and Rawal 2000;Grundy et al 2001;Sueters et al 2005), although the PAX3:FOXO1 translocation has been detected in rare neonatal instances (Rodriguez-Galindo et al 2001).…”
Section: Discussionmentioning
confidence: 82%
“…34,35 Pax3-Foxo1 is found in 70% ARMS cases and is considered a strong predictor of poor prognosis, while fusion-negative ARMS have better resolution and are clinically and molecularly indistinguishable from the larger group of ERMS in the majority of patients. 36 Because of the ability of Pax3-Foxo1 to drive the transcription of genes like fibroblast growth factor receptor 4 (FGFR4) and insulin-like growth factor 2 (IGF-2), fusionpositive RMS are characterized by sustained activation of the RTK/RAS/phosphatidylinositol-3-kinase (PI3K) axis; 33 in addition, these tumors often carry high copy number of N-Myc gene [37][38][39] and exhibit IGF-2 overexpression due to loss of imprinting (LOI) at 11p15.5 locus 40 (Fig. 2).…”
Section: Rhabdomyosarcomamentioning
confidence: 99%